DISRUPSI MENURUT FRANCIS FUKUYAMA DAN IMPLIKASINYA PADA TATANAN SOSIAL - Pita Roja, Williams Flavian (Seminari Tinggi St. Fransiskus Xaverius Ambon, 2023)
Technology is advancing faster than humans can regulate it. All around us, we can see the positive and negative developments brought about by the ever-evolving technology. Experts refer to these modifications as disruptions. This article will examine disruption through the eyes of Francis Fukuyama. Fukuyama, who views disruption from a more complicated social perspective, does not share Christensen's view that it has a positive influence, particularly economically. Fukuyama called this change The Great Disruption. A significant change that led to a significant shift in the social order. Fukuyama breaks it down into three main categories: rising crime or criminality, deteriorating family dynamics, and a growing circle of distrust. To deal with this shift, people must recognize that they are social beings with the ability to organize themselves, which is a return to human nature. In practical terms, social capital and the social order provide two grounds for support. The first is biological support, which comes from the very essence of humanity. The second is human reasoning ability, which comes up with solutions to issues of social collaboration on its own.